On the constrained controllability of dynamical systems with multiple delays in the state - Sikora, Beata (Zielona Góra: Uniwersytet Zielonogórski)
Linear stationary dynamical systems with multiple constant delays in the state are studied. Their relative and approximate controllability properties with constrained controls are discussed. Definitions of various types of controllability with constrained controls for systems with delays in the state are introduced.
Keywords: delay systems; constrained controllability; control; constraints; asymptotic stability